PENGARUH E-MODUL TERHADAP PEMAHAMAN KONSEP LETAK GEOGRAFIS INDONESIA DI SD MARGAMULYA DAN SD 1 KARANGSAMBUNG - Haliza Nurulwapa; Elan; Pidi Mohamad Setiadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Understanding the concept of Indonesia's geographical location is essential for elementary school students, as it helps them express ideas, opinions, and understand the country's richness. However, IPAS (Social and Natural Sciences) learning at SDN Margamulya and SDN 1 Karangsambung faces several challenges, mainly due to ineffective teaching methods. To address this issue, this study introduces an Android-based E-Module as an innovative solution. The aim is to describe students' understanding before and after using the E-Module and to measure its impact. This research employed a pre-experimental method with a one-group pretest-posttest design, and data were collected through tests. Results from Grade V showed that before using the E-Module, no students were in the "very good" category, only 2 in the "good" category, 9 in "fair," and 8 in "poor." After using the E-Module, there was a significant improvement: 8 students reached the "very good" category, 11 were "good," 1 was "fair," and none were in the "poor" category. Based on hypothesis testing, the use of Android-based E-Modules had a positive effect on students' understanding of IPAS concepts.